How resource nationalism hinders development: the institutional roots of the economic recession in Venezuela - Fontaine, Guillaume; Caviedes, Cecilia Medrano (Revista do Serviço Público, 2016)
How do institutions allow governments to manage dramatic variations of oil rents, and how do these variations impact public institutions is the twofold problem addressed here. We contend that high dependence on oil combined with low political accountability increases the economic vulnerability to external shocks. We sustain our argument with the analysis of the fiscal policies implemented in Venezuela under the administration of Hugo Chávez (1999-2012). A process tracing methodology focuses on the policy design of fiscal policies through the selection of instruments embedded in the Public Finance Management system (PFM), using a typology of the state´s resources of information, authority, treasure and organization. During this period, the constitutionalization of the resource nationalism acted as a trigger to change fiscal policies through four major reforms including the creation of a highly centralized PFM, the takeover of the Central Bank, the reform of oil legal framework and the takeover of the national oil company, PDVSA. All of these reforms converged towards the elimination and/or manipulation of the instruments of political accountability, allowing discretional management of oil rents and hampering the government´s capacity to react to the oil price plunge, which ultimately led to the current economic recession.